Asthma Education Program for First Nations Children: An exemplar of the Knowledge-to-Action Framework - Maureen L Douglas; Shawna L McGhan; Danielle Tougas; Nancy Fenton; Christopher Sarin; Oxana Latycheva; A Dean Befus (Canadian Respiratory Journal)
BACKGROUND: The prevalence of asthma in Aboriginal children is 6% to 14%. Gaps in knowledge regarding asthma and its management exist in First Nations (FN) communities, and culturally relevant education and resources are required. Studies have recommended that the children’s asthma education program, the ‘Roaring Adventures of Puff’, be modified through partnership with FN communities to be culturally appropriate.